Changes in predictive cuing modulate the hemispheric distribution of the P1 inhibitory response to attentional targets. (May 2017) - Lasaponara, Stefano; D' Onofrio, Marianna; Dragone, Alessio; Pinto, Mario; Caratelli, Ludovica; Doricchi, Fabrizio
Abstract: Brain activity related to orienting of attention with spatial cues and brain responses to attentional targets are influenced the probabilistic contingency between cues and targets. Compared to predictive cues, cues predicting at chance the location of targets reduce the filtering out of uncued locations and the costs in reorienting attention to targets presented at these locations.Slagter et al. (2016) have recently suggested that the larger target related P1 component that is found in the hemisphere ipsilateral to validly cued targets reflects stimulus-driven inhibition in the processing of the unstimulated side of space contralateral to the same hemisphere. Here we verified whether the strength of this inhibition and the amplitude of the corresponding P1 wave are modulated by the probabilistic link between cues and targets. Healthy participants performed a task of endogenous orienting once with predictive and once with non-predictive directional cues. In the non-predictive condition we observed a drop in the amplitude of the P1 ipsilateral to the target and in the costs of reorienting. No change in the inter-hemispheric latencies of the P1 was found between the two predictive conditions. The N1 facilitatory component was unaffected by predictive cuing. These results show that the predictive context modulates the strength of the inhibitory P1 response and that this modulation is not matched with changes in the inter-hemispheric interaction between the P1 generators of the two hemispheres. Highlights: Non-predictive directional cues reduce the filtering out of uncued target locations. The P1 ipsilateral to target side reflects inhibition of contralateral no-target side. We tested whether cue predictiveness modulates the amplitude of the ipsilateral P1. Non-predictive cues reduced the ipsilateral P1 with no effect on its latency or on N1. The strength of P1-related inhibition depends on the probabilistic cue-target link.